Effect of vitamin D on the pregnancy and the health of newborns and infants: state-of-the-art - I.N. Zakharova; S.V. Mal'tsev; V.V. Zubkov; V.A. Kur'yaninova; A.V. Dmitriev; L.I. Mal'tseva; N.E. Verisokina; L.Ya. Klimov; E.N. Vasil'eva; S.I. Malyavskaya; A.L. Zaplatnikov (LCC «Medicine-Inform», 2020)
I.N. Zakharova1, S.V. Mal'tsev1, V.V. Zubkov2, V.A. Kur'yaninova3, A.V. Dmitriev4, L.I. Mal'tseva5, N.E. Verisokina3, L.Ya. Klimov3, E.N. Vasil'eva6, S.I. Malyavskaya7, A.L. Zaplatnikov1 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2V.I. Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology, Moscow, Russian Federation 3Stavropol State Medical University, Stavropol, Russian Federation 4Ryazan State Medical University, Ryazan, Russian Federation 5Kazan State Medical Academy - Branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 6I.N. Ul'yanov Cheboksary State University, Cheboksary, Russian Federation 7North State Medical University, Arkhangelsk, Russian Federation This paper reviews the effects of vitamin D deficiency on pregnant women and newborns. It was demonstrated that vitamin D deficiency in pregnant women is associated with higher risks of threatened preterm labor, placental insufficiency, preeclampsia, gestational diabetes, bacterial vaginosis, and impaired uterine contractility as well as higher rate of C-sections. Vitamin D insufficiency in newborns is associated with inadequate bone mineralization and also results in metabolic disorders, hypocalcemic seizures, bronchopulmonary dysplasia, necrotic enterocolitis, sepsis, mental and developmental disorders, and higher risks of various (infectious, allergic etc.) disorders. Optimal vitamin D dosing regimen in pregnant women and newborns is discussed. Keywords: pregnancy, vitamin D, vitamin D insufficiency, newborn, complications of pregnancy, preeclampsia, gestational diabetes. For citation: Zakharova I.N., Mal'tsev S.V., Zubkov V.V. et al. Effect of vitamin D on the pregnancy and the health of newborns and infants: state-of-the-art. Russian Journal of Woman and Child Health. 2020;3(3):174-181. DOI: 10.32364/2618-8430-2020-3-3-174-181.